2018
DOI: 10.1155/2018/9804291
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Boundary-Type Meshless Method for Modeling Geofluid Flow in Heterogeneous Geological Media

Abstract: A novel boundary-type meshless method for modeling geofluid flow in heterogeneous geological media was developed. The numerical solutions of geofluid flow are approximated by a set of particular solutions of the subsurface flow equation which are expressed in terms of sources located outside the domain of the problem. This pioneering study is based on the collocation Trefftz method and provides a promising solution which integrates the T-Trefftz method and F-Trefftz method. To deal with the subsurface flow pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The corresponding Gardner parameters were calculated using (12). From Figure 12, it is found that the SWCC based on the Gardner model provides acceptable agreement with the van Genuchten model.…”
Section: Geofluidsmentioning
confidence: 99%
See 1 more Smart Citation
“…The corresponding Gardner parameters were calculated using (12). From Figure 12, it is found that the SWCC based on the Gardner model provides acceptable agreement with the van Genuchten model.…”
Section: Geofluidsmentioning
confidence: 99%
“…Consequently, shallow landslides may often occur within the vadose zone under unsaturated soil conditions [5][6][7]. The prediction of flow in transient conditions is important in engineering practice while considering the stability of unsaturated soil slopes [8][9][10][11][12] or poromechanical coupling influence for rainfall-induced shallow landslides in unsaturated soils [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…, f j denote the boundary values for Dirichlet and Neumann boundary conditions, respectively. In this article, we adopt the domain decomposition method (DDM) [37,38] to solve the nonlinear moving boundary problems in heterogeneous geological media. The DDM is commonly used to solve the problem with different physical characteristics in each subdomain.…”
Section: The Characteristic Lengthmentioning
confidence: 99%
“…In the recent past, numerical modeling has gained more interest and has become an important tool for defining and tackling geological problems [22][23][24]. Technological progress has been simplifying the process of understanding soil behavior under different loading perspectives [25].…”
Section: Introductionmentioning
confidence: 99%